Chemical Investigation of Paederia foetidae (Rubiaceae) - Uddin, N.; Hossain, M.K.; Haque, M.R.; Hasan, C.M. (Asian Journal of Chemistry, 2012)
Chemical investigation on the methanol extract of Paederia foetidae, using vacuum liquid chromatography resulted in the isolation of ethyl p-methoxy-trans-cinnamate. The structure was established by extensive spectral analysis (PMR, CMR, 2D NMR and MS etc.) and comparing with the published data. This is the first report of this compound from Rubiaceae family.